2018
DOI: 10.1021/acsami.8b11234
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electron Mobility in an All-Acceptor Napthalenediimide-Bithiazole Polymer Semiconductor with Large Backbone Torsion

Abstract: An all-acceptor napthalenediimide-bithiazole-based copolymer, P(NDI2OD-BiTz), was synthesized and characterized for application in thin-film transistors. Density functional theory calculations point to an optimal perpendicular dihedral angle of 90°between acceptor units along isolated polymer chains; yet optimized transistors yield electron mobility of 0.11 cm 2 /(V s) with the use of a zwitterionic naphthalene diimide interlayer. Grazing incidence X-ray diffraction measurements of annealed films reveal that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…In the light of different acceptor substrates, some reactions differ, and five aspects should be considered here. Firstly, the organotin based on WA is the preferred substrate [6,41,46,53,54], since the tinned substrate for SA is more difficult to synthesize and purify, apart from A2 with a M n of 32.0 kDa which was coplymerized using the tin reagent of SA [27]. Secondly, the option of the catalyst can be changed according to different substrates.…”
Section: Sa-wa-type Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…In the light of different acceptor substrates, some reactions differ, and five aspects should be considered here. Firstly, the organotin based on WA is the preferred substrate [6,41,46,53,54], since the tinned substrate for SA is more difficult to synthesize and purify, apart from A2 with a M n of 32.0 kDa which was coplymerized using the tin reagent of SA [27]. Secondly, the option of the catalyst can be changed according to different substrates.…”
Section: Sa-wa-type Polymersmentioning
confidence: 99%
“…To achieve high-performance electron-transporting polymers, the molecular structures and design rules in OFETs and PSCs are slightly different due to the different device structures and principles. Firstly, for the design of high-performance OFET semiconductor materials, molecules with the minimal steric hindrance and the excellent coplanarity of the main chain can increase the overlap of p-orbitals between molecules, which values for improving mobility [23][24][25][26][27]. For PSCs, the molecular structure also needs the main-chain coplanarity but not as important as the n-type semiconductor in OFETs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15a] However,a ll reported BTI-based polymers were synthesized exclusively from dibrominated BTI monomer,which could limit polymer synthetic routes,m olecular weights,a nd structures.I tw as found that Yamamoto,Ullman, and Stille couplings could also be applied for the synthesis of A-A type polymers,h owever the resulting polymers generally showed low number-average molecular weight (M n )a nd (or) structural defects,w hich led to OTFT performance variation over aw ide range. [15a, 21a,b, 22] Marder et al first reported distannylated electron-deficient NDIs, [23] which were then widely used in the development of n-type oligomers and A-A copolymers, [24,25] showing low-lying FMO levels.W hen applied in OTFTs,p olymers PSN-NDI and PBBT-NDI [25b] (Figure 1b)y ielded moderate m e,OTFT values of 0.0011 and 0.039 cm 2 V À1 s À1 ,r espectively, owing to their twisted backbone,a nd the devices based on PBBT-NDI exhibited long-term stability.T oa lleviate steric hindrance associated with NDI, vinylene linker was attached and an ovel NDI monomer containing two (tributylstannyl)vinyl groups was reported by Heeney [26] and Briseno, [27] independently.T he bis(tributylstannyl)vinyl NDI enables development of high-performance unipolar n-type polymers. Polymer P3 featured planar backbone and the OTFTs showed an excellent m e,OTFT up to 3.87 cm 2 V À1 s À1 with ar emarkable stability in air,a nd P4-based devices exhibited af urther increased m e,OTFT of 7.16 cm 2 V À1 s À1 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Several moieties based on thiazole, such as monothiazole, bithiazole, thiazolothiazole, and benzobisthiazole, have been exploited to synthesize donor–acceptor alternating copolymers, and have yielded high performance in organic electronic devices. [ 15–27 ] The 2,2′‐bithiazole unit has promising features that could advance the search for electron–transport conjugated polymers. [ 18 ] The presence of electronegative nitrogen atoms lowers the lowest unoccupied orbital (LUMO) energy in comparison to analogues that consist of electron‐rich units such as thiophene derivatives, and yield transport characteristics that are dominantly n‐type.…”
Section: Introductionmentioning
confidence: 99%